2006
DOI: 10.1002/j.2168-9830.2006.tb00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Students' Perceptions of and Attitudes Towards Cheating

Abstract: Academic dishonesty has become a serious problem at institutions of higher learning. This is particularly true in engineering where, according to previous research, engineering undergraduates are among the most likely to cheat in college. To investigate this concern, the authors embarked on a research project whose goal was to develop a better understanding of what students and faculty perceive as cheating and to use this knowledge to help instructors and institutions increase the level of academic integrity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
2
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(131 citation statements)
references
References 37 publications
10
100
2
9
Order By: Relevance
“…A large portion of the literature in engineering education related to ethics has focused on content and pedagogy and general ethical (or unethical) behaviors such as cheating or participation in pro-social activities 2,3,4,5,6 . However, an increasing number of studies are investigating foundational considerations such as student levels of moral development or student perceptions of, and attitudes toward, social and ethical responsibility.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…A large portion of the literature in engineering education related to ethics has focused on content and pedagogy and general ethical (or unethical) behaviors such as cheating or participation in pro-social activities 2,3,4,5,6 . However, an increasing number of studies are investigating foundational considerations such as student levels of moral development or student perceptions of, and attitudes toward, social and ethical responsibility.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…The E 3 team of researchers used PACES-1 to study selfreported incidence and perceptions among engineering students and the team has published in a number of engineering education and higher education conference proceedings and journals [5] [22]. In 2006, the E 3 team reported that 96% of surveyed students admitted to knowingly engaging in behaviour widely regarded as cheating.…”
Section: The Prevelance Of Academic Dishonesty In Engineeringmentioning
confidence: 99%
“…PACES-1 was used in a survey of 643 undergraduate engineering students at 11 institutions in the US and abroad [5]. It was a general investigation into undergraduate cheating and what students and faculty consider to be academic dishonesty.…”
Section: Introductionmentioning
confidence: 99%
“…One treats word for word plagiarism regardless of degree in a similar manner as other instances of "academic dishonesty" such as copying on exams or buying papers from online paper mills (Brown 1994;Brown 1996;Carpenter, Harding, Finelli, Montgomery, & Passow 2006;McCabe 1997). Another perspective views it as a continuum of compositional strategies utilized by both novice and expert writers originating from a complex of reasons, few of which may have anything to do with deception or dishonesty.…”
Section: Literature Reviewmentioning
confidence: 99%